Putting CLIL into practice - Ball, Phil, ....-; Kelly, Keith, ....-; Clegg, John, ....- (Oxford : Oxford University Press, 2019)
Putting CLIL into Practice 1e editie is een boek van Phil Ball uitgegeven bij Oxford University Press. ISBN 9780194421058 Putting CLIL into Practice offers a new methodological framework for the CLIL classroom, focusing on how to guide input and support output. Full of real-life examples and practical guidelines, the book provides support to both novice and experienced CLIL teachers.
This substantial volume offers a vast array of ideas, activities and checklists on all aspects of CLIL that bear witness to the authors' concern with conceptual foundations as well as their creativity and experience as CLIL consultants and language-teaching experts. Without doubt, this book is an important contribution to the advancement of teaching methodology in CLIL and will help spread the word about good pedagogy in CLIL contexts around the world. * Christiane Dalton-Puffer, ELT Journal * Contains much relevant advice and a wealth of useful suggestions... This book is very important because it is a practical guide to the way that English language education is heading. * Modern English Teacher * this substantial volume offers a vast array of ideas, activities and checklists on all aspects of CLIL that bear witness to the authors' concern with conceptual foundations as well as their creativity and experience as CLIL consultants and language-teaching experts. Without doubt, this book is an important contribution to the advancement of teaching methodology in CLIL and will help spread the word about good pedagogy in CLIL contexts around the world.